Knowledge-Based Country Programs : An Evaluation of World Bank Group Experience - Independent Evaluation Group (Washington, DC: World Bank, 2016)
The World Bank Group is currently engaged in reflection and debate on how to improve the delivery of development support. Part of this debate concerns strengthening the knowledge agenda. The findings of this evaluation are particularly relevant because they speak directly to questions that the institution is deliberating. In particular, they address four key aspects of the “science of delivery”: the role of local partners or local knowledge hubs; consultation with clients and other stakeholders in the process of designing knowledge services; delivery of knowledge on issues that are relevant to the client; and improving the way the Bank Group learns from upper-middle-income countries and intermediating this knowledge to other countries.